OBSTETRIC VIOLENCE AN ANALYSIS OF SOCIAL REPRESENTATIONS - Oliveira Soares, Mayla; Ribeiro do Nascimento, Sabrina; Lúcia Cristóvão da Silva, Vera; Sales Pereira Silva, Késsia; Silva de Oliveira, Marcelo (Revista Gênero e Interdisciplinaridade, 2022)
The aim of this study is to investigate how obstetric violence occurs in the Brazilian context on the basis of gender, race and social class. In this way, it seeks to understand how social exclusion can be a contributing risk factor for the violation of women’s rights in their pregnancy-puerperal cycle. The present literature suggests that the context of social vulnerability and the power relations fostered in the hospital environment are configured as practices that threaten a healthy pregnancy and contribute to the occurrence of this reality in Brazil.